2010
DOI: 10.2217/nnm.10.99
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin-Mediated Targeting of Bacteriophage HK97 Nanoparticles Into Tumor Cells

Abstract: Aims Next-generation targeted nanodevices are currently under development for imaging and therapeutic applications. We engineered HK97 viral nanoparticles (VNPs) for tumor cell-specific targeting. Methods A combination of genetic and chemical engineering methods were developed and applied to generate dual-labeled HK97 cysteine mutant particles displaying transferrin and fluorescent labels. The targeting properties of transferrin-conjugated VNPs were evaluated by in vitro experiments using different cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 59 publications
3
49
0
Order By: Relevance
“…A distinct advantage of bacteriophage HK97 is that, due to the different maturation states of the bacteriophage capsid head, a range of HK97 particles with different sizes, internal capacity, stability and dynamics could be explored for cell uptake studies. Confocal imaging confirmed that the functionalized HK97 particles were internalized in cancer cells via endocytosis in clathrin-coated pits, which were subsequently targeted and localized to the endolysosomal compartment (Huang et al, 2011).…”
Section: Molecular Detectionmentioning
confidence: 83%
“…A distinct advantage of bacteriophage HK97 is that, due to the different maturation states of the bacteriophage capsid head, a range of HK97 particles with different sizes, internal capacity, stability and dynamics could be explored for cell uptake studies. Confocal imaging confirmed that the functionalized HK97 particles were internalized in cancer cells via endocytosis in clathrin-coated pits, which were subsequently targeted and localized to the endolysosomal compartment (Huang et al, 2011).…”
Section: Molecular Detectionmentioning
confidence: 83%
“…151 CPMV displaying peptide F56, which was discovered through phage display, has been used to target vascular endothelial growth fa ctor receptor-1 (VEGFR-1), with accumulation throughout the tumor observed compared to no detectable uptake of non-targeted particles. 99 Other options that have been explored include FR targeting with folic acid (FA), 164, 184, 185 TfR with transferrin, 186 and prostate specific membrane antigen (PSMA) with a PSMA antibody. 187 In recent years, a target that has been approached from many angles is epidermal growth factor receptor (EGFR), an important biomarker overexpressed on many malignant cell types.…”
Section: Applications Of Virus-based Particlesmentioning
confidence: 99%
“…The HK97 fold has been detected in every tailed phage capsid that has been imaged at sufficient resolution, including P22 11; 12; 13 , T4 14 , λ 15 , ϕ29 16 , T5 17; 18 , P2/P4 19 , epsilon15 20 , T7 21; 22 , the tailed-phage-like archaevirus HSTV-1 23 , in the base layer of the Herpesvirus (HSV1) major capsid protein 24 and in the bacterial comparments known as encapsulins 25 . With renewed interest in phage therapy to combat multiple-drug-resistant bacterial pathogens 26; 27; 28 , and an emerging interest in using bacteriophage capsids as platforms for nanotechnology 29 (http://www.nano.gov/) directed to the treatment of disease 30; 31 and the creation of new technologies 32; 33; 34; 35 , it is important to have a deep understanding of capsid structures and assembly pathways in order that they can be manipulated and utilized to the greatest extent.…”
Section: Introductionmentioning
confidence: 99%